The impact of maintenance policies on some items of ISO (9001-2000): a survey study in industrial companies in Iraq - Mokhef, Mokhef Abd Alhussin; Supeni, Eris Elianddy; Abdul Jalil, Nawal Aswan (Eclat Research Publication, 2015)
The influence of maintenance policy on the industrial sector is highly important, where there is a significant correlation between maintenance policies and some of the items related to international standard (ISO 9001- 2000) such as infrastructure, work environment, control of the production and service operations, and the adjustment of the measurement and monitoring tools. The aim of this study is to provide the intellectual and workable framework that relies on the arguments of researchers and those interested in the fields of management, production and engineering operations to highlight the role of maintenance policies in contributing to the achievement of quality. The industrial and governmental sectors were selected in the province of Nineveh as an arena to do the field work. The sample of the study comprises of six governmental and industrial companies. Questionnaires are used as the main tool for data collection. The study shows the need for sites with appropriate physical working conditions of temperature, humidity, and ventilation to do work in order to ensure the quality of performance through the maintenance policies.